‘WARUGA’ SEBAGAI DAYA TARIK WISATA DI DESA SAWANGAN, KABUPATEN MINAHASA UTARA - Mangolo, Mikhael Credo Samuel; Sukaatmadja, I Putu Gde; Pujaastawa, Ida Bagus Gde (Jurnal Master Pariwisata (JUMPA); Volume 04, Nomor 01, Juli 2017, 2017)
Waruga grave stone coffin is a cultural heritage of Minahasa that have been designated as a cultural attraction. The purpose of this study was to describe the internal and external factors that influence the development of the Waruga Cultural Heritage as a tourist attraction, as well as formulate the development strategy for the tourist attraction of Waruga Cultural Heritage in realizing the sustainable tourism. This study used qualitative descriptive analysis using the collecting data techniques through observation, in-depth interview, documentation, and literature study. Informants were determined by purposive sampling and the acquired data were analyzed using SWOT analysis. The results of this study indicated that in order to maximize the development of the tourist attraction as well as realizing sustainable tourism to the Waruga Cultural Heritage, it is necessary to develop the strategies and programs such as empowerment of local communities, develop the facilities and infrastructure of the tourist attraction, improve the safety and convenience for tourists, protection against the cultural heritage, as well as develop the institutional and human resources.